PERANCANGAN FASILITAS KERJA PADA AKTIVITAS MEMAHAT DI INDUSTRI KECIL BATU ALAM - Maria Chandra Dewi Kurnianingtyas; L. Triani Dewi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2014)
The techniques and the principles of work system can improve efficiency and work productivity. Work system consists of several work elements. They are man, material, environment, method, and equipment. The elements is interconnected each others. The elements was influent efficiency and work productivity. Efficiency is important in the work system. The purposes of the research is design of work facilitiess, so that can improve work productivity. Inefficiency of work motion and work facility can influent work productivity. Work posture can analyzed RULA method. The score of work postures were 5,6, and 7. The high scores have indicate that the facilities must be investigated and must be changed. The workers need to work facility to prevent musculoskeletal injury.